Primary auditory symptoms in patients with normal peripheral hearing sensitivity: Redefining hearing loss. (2nd January 2016) - Shinn, Jennifer; Long, Ashleigh; Rayle, Chris; Bush, Matthew
Abstract: Objective: Hearing loss has historically been defined as a 'sudden or gradual decrease in how well you can hear' (1). This is characterized by a set of strict criteria which evaluate the intensity level at which one hears critical frequencies needed to understand speech. The purpose of this investigation was to determine the number of patients in an otolaryngology practice at an academic medical center who present with auditory complaints yet demonstrate normal audiograms. Study design: The study was a retrospective chart review that examined 498 patients over a four-year period. Results: Results demonstrated that while nearly half of the patients' primary complaint was hearing loss (48%), a large number also reported tinnitus (39%) and auditory processing difficulties (13%). Conclusions: Patients who report concerns regarding abnormal auditory perceptions (hearing loss, tinnitus and/or auditory processing) yet present with normal peripheral hearing sensitivity via pure tone audiometry, represent an important clinical population that deserves further attention.